Study on the osmotic pre-treatment and infrared radiation on drying kinetics and colour changes during drying of agricultural products - S. K. Chou,; K. J. Chua,; A. S. Mujumdar; M. Tan, and; S. L. Tan (Universitas Gadjah Mada, 2001)
A combination of intermittent infrared and continuous convection heating was used to dehydrate various osmotically pretreated sample of potato (in solutions of 10%, 20% and 30% NaCl) and pineapple (in solutions of 30%, 50%, 70% Brix). In one set of runs, the infrared source was turned on and off sequentially according to a predetermined time schedule. In the other set, a thermocouple located on the surface of the drying slice exposed to the radiant heat flux measured the temperature continuously and cut off the infrared source automatically when the surface temperature reached 36 to 45°C. The effect of osmotic-IR conditions on colour changes of potato, pineapple and apple was investigated. With appropriate choice of infrared intermittency as well as osmotic pretreatment, it is possible to reduce the overall colour change while maintaining high drying rates. Results from the temperature feedback system indicated no measurable colour degradation occurred despite faster drying kinetics, reduction in drying times and minimisation in product shrinkage.